ประสิทธิผลของการประชาสัมพันธ์เพื่อการตลาดของนวนิยายนำเข้าจากประเทศญี่ปุ่นประเภทไลท์โนเวล - พฤพลอย ประภาจิตร์ (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
The purposes of this research were 1) to study the marketing public relations of imported light novel by publishers in Thailand. 2) to compare light novel’s media exposure of consumers with different demographic characteristics. 3) to compare light novel’s buying behavior of consumers with different demographic characteristics. 4) to study the effectiveness of marketing public relations on Japan - imported light novel. 5) to study the factor that affected the most to light novel’s buying behavior. The study was based on qualitative and quantitative methods. 1) In-depth Interview with public relations officers of three publishers Japan - imported light novel and Documentary research. 2) Questionnaires used to collect data from 400 respondents aged 13-30 years old in Bangkok. The data were statistically analyzed by using frequency distribution, percentage, standard deviation, Independent-samples T-test, One-way Anova, Correlation and Multiple regression. The findings in qualitative method showed that that three publishers used thirteen method to reach their customers including the use of marketing mix, online media, event marketing, Exhibition booth, co-operated websites, corporate social responsibility, sales person, Identity Media, plans prepared for negative news, television, owned magazine review, mass communication and commercial inside light novel books. The results of quantitative method revealed that consumers with different demographic characteristics had different light novel’s media exposure and buying behavior. In the analysis of the effectiveness of marketing public relations on Japan - imported Light Novel, the study showed that light novel’s marketing public relations had a relationship with light novel’s buying behavior in the same direction. Readers who had more light novel’s media exposure would also have more light novel’s buying behavior as well. From the research, the amount of "Like" indicating subscription of three publisher Facebook fanpages showed that their marketing public relations were able to reach their targeted consumers and received good response by causing buying behavior. Regarding to the influence of studied factors that affected buying behavior of light novel consumers, the result indicated that marketing public relations was the most influential factor to buying behavior of consumers followed by products, places, and price. Overall, the result of this research would be beneficial to light novel publishers in Thailand using it as a guide to further improve their business growth.